Nanocrystalline cobalt ferrite powders by spray solution combustion synthesis - Minin, Roman V.; Zhuravlev, Victor A.; Lapshin, Oleg V.; Itin, Volya I.; Svetlichnyi, Valerii A. (International journal of self-propagating high-temperature synthesis)
Abstract: Nanocrystalline cobalt ferrospinel powders were prepared by spray solution combustion synthesis (SSCS) and their structural and magnetic properties were characterized by mathematical modeling and experimentally. The magnitude of specific saturation magnetization of the synthesized materials was somewhat higher than that typical of bulk materials whereas the field of magnetocrystalline anisotropy and Curie temperature, noticeably smaller. @ 2020, Allerton Press, Inc.